DEVELOPING INDICATORS FOR MONITORING TOURISM AND SUSTAINABILITY IN RAMESWARAM, A BUFFER AREA IN THE GULF OF MANNAR MARINE BIOSPHERE RESERVE, INDIA - MURAL, Jana; POYYAMOLI, Gopalsamy (Journal of Environmental Management and Tourism; Vol 1 No 2 (2010): JEMT Volume I Issue 2(2) Winter 2010, 2016)
India’s tourism sector is growing rapidly but has many challenges to tackle. To achieve and sustain the projected growth levels, the tourism sector in India needs to seriously look at sustainability. Many popular tourism destinations in the country are situated in ecologically sensitive areas with a very high footprint. Gulf of Mannar Marine Biosphere Reserve (GOMBR) is the first established Marine Biosphere in the country. Several tourism destinations situated closely to the GOMBR have greater negative influence on biodiversity, social and economic fabric of local communities. Rameswaram Island ranks top among them. Present tourism in the island threatens biodiversity and sustainable development of the destination areas. As there is no established mechanism to regulate tourism in the ecologically sensitive buffer zones of India, the research attempted to define sustainability for the destination and creates indicators for monitoring tourism using the pressure-state-response (PSR) model. The paper elaborates the process involved in defining indicators with justifications. As pointed out by the study, objectively verifiable indicators could be used to monitor tourism in many Protected Areas (PA) and ecologically sensitive areas in the country to pave a way for regulation of tourism. However improvements are needed in selecting and evaluating the effectiveness of indicators to suit site specific conditions.